PTR-QMS versus PTR-TOF comparison in a region with oil and natural gas extraction industry in the Uintah Basin in 2013 - C Warneke; Veres, P.; Murphy, S. M.; Soltis, J.; Field, R. A.; Graus, M. G.; Koss, A.; Li, S. -M.; Li, R.; Yuan, B.; Roberts, J. M.; de Gouw, J. A. (ATMOSPHERIC MEASUREMENT TECHNIQUES, 2015)
Here we compare volatile organic compound (VOC) measurements using a standard proton-transfer-reaction quadrupole mass spectrometer (PTR-QMS) with a new proton-transfer-reaction time of flight mass spectrometer (PTR-TOF) during the Uintah Basin Winter Ozone Study 2013 (UBWOS2013) field experiment in an oil and gas field in the Uintah Basin, Utah. The PTR-QMS uses a quadrupole, which is a mass filter that lets one mass to charge ratio pass at a time, whereas the PTR-TOF uses a time of flight mass spectrometer, which takes full mass spectra with typical 0.1 s-1 min integrated acquisition times. The sensitivity of the PTR-QMS in units of counts per ppbv (parts per billion by volume) is about a factor of 10-35 times larger than the PTR-TOF, when only one VOC is measured. The sensitivity of the PTR-TOF is mass dependent because of the mass discrimination caused by the sampling duty cycle in the orthogonal-acceleration region of the TOF. For example, the PTR-QMS on mass 33 (methanol) is 35 times more sensitive than the PTR-TOF and for masses above 120 amu less than 10 times more. If more than 10-35 compounds are measured with PTR-QMS, the sampling time per ion decreases and the PTR-TOF has higher signals per unit measuring time for most masses. For UBWOS2013 the PTR-QMS measured 34 masses in 37 s and on that timescale the PTR-TOF is more sensitive for all masses. The high mass resolution of the TOF allows for the measurements of compounds that cannot be separately detected with the PTR-QMS, such as oxidation products from alkanes and cycloalkanes emitted by oil and gas extraction. PTR-TOF masses do not have to be preselected, allowing for identification of unanticipated compounds. The measured mixing ratios of the two instruments agreed very well (R-2 >= 0.92 and within 20 %) for all compounds and masses monitored with the PTR-QMS.